Eco-Innovation in Global Hotel Chains: Designs, Barriers, Incentives and Motivations - Vanessa de Oliveira Menezes; Sieglinde Kindl da Cunha (BBR: Brazilian Business Review)
ABSTRACT This article aims to verify the reality of eco-innovations developed by global hotel chains, highlighting the innovative designs employed by these organizations, the barriers and incentives faced by these companies and motivations to invest in innovations for this purpose. This multiple case study, of qualitative, descriptive and sectional nature used the thematic content analysis, using the NVivo® software to analyze some of the data obtained and supported on the triangulation of information to increase the reliability of the results. The data sources were empirical research, gathered through interviews and questionnaires, and documentary research. We found that the chains under study develop a large number of ecoinnovations in their companies, and most of them are end-of-pipe. In the respondents´ view, there are more barriers than incentives for the development of this type of innovation and the development is driven in large part as a mean to gain competitive advantage.